2020
DOI: 10.1016/j.trf.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors underpinning unsafe driving: A systematic literature review of car drivers

Abstract: Objectives: The purpose was to provide a systematic review of the literature related to the personality and well-being of social, domestic, pleasure and commuting (SDP&C) car drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 74 publications
(62 reference statements)
0
12
1
Order By: Relevance
“…These effects were observed in both cross-sectional and longitudinal studies (Galvin and Smith, 2015;Nelson and Smith, 2016). The model appears to be very robust in that it has been supported in studies of general working samples (Nor and Smith, 2018;Omosehin, 2021), working mothers (Smith & James, 2021), office workers Langer, Tailor & Smith, 2019), university staff (Williams, Thomas and Smith, 2017), teachers (Smith and James, 2021), nurses Williams, Pendlebury & Smith, 2021), blue collar workers , transport workers Bowen, Budden & Smith, 2020), the coastguard (Kingdom & Smith, 2011), the police (Nelson, 2017), trainee mental health staff (Galvin, 2016), firefighters (Butler et al, 2021), call center staff (McFarlane, 2022), those working away from home for extended periods (Smith, 2021b), and sports organizations (Neil, McFarlane & Smith, 2016). The model has been used in studies in Italy (Capasso, Zurlo & Smith, 2016Zurlo, Valone & Smith, 2018), China (Zhang & Smith, 2021), the USA (Ahmad et al, 2018a, b), Jamaica (Nelson, 2017), Kuwait (Alheneidi, 2020) and Nigeria (Omosehin, 2021).…”
Section: The Cardiff Wellbeing At Work Programmentioning
confidence: 72%
“…These effects were observed in both cross-sectional and longitudinal studies (Galvin and Smith, 2015;Nelson and Smith, 2016). The model appears to be very robust in that it has been supported in studies of general working samples (Nor and Smith, 2018;Omosehin, 2021), working mothers (Smith & James, 2021), office workers Langer, Tailor & Smith, 2019), university staff (Williams, Thomas and Smith, 2017), teachers (Smith and James, 2021), nurses Williams, Pendlebury & Smith, 2021), blue collar workers , transport workers Bowen, Budden & Smith, 2020), the coastguard (Kingdom & Smith, 2011), the police (Nelson, 2017), trainee mental health staff (Galvin, 2016), firefighters (Butler et al, 2021), call center staff (McFarlane, 2022), those working away from home for extended periods (Smith, 2021b), and sports organizations (Neil, McFarlane & Smith, 2016). The model has been used in studies in Italy (Capasso, Zurlo & Smith, 2016Zurlo, Valone & Smith, 2018), China (Zhang & Smith, 2021), the USA (Ahmad et al, 2018a, b), Jamaica (Nelson, 2017), Kuwait (Alheneidi, 2020) and Nigeria (Omosehin, 2021).…”
Section: The Cardiff Wellbeing At Work Programmentioning
confidence: 72%
“…Several systematic reviews of the literature have found that poor physical and mental health in medical professionals is associated with less safe patient care [100,101]. In the case of bus drivers, a "good" physical and psychological state is associated with greater safety on the road [102,103], while in the group of production workers it means fewer mistakes at work and higher performance [104].…”
Section: Discussionmentioning
confidence: 99%
“…Driving is a complex activity that requires integration of physical, cognitive and sensory functions and is influenced both by internal human psychological factors and external environment factors. The existing literature summarizes factors influencing driving performance into two sets: (1) driver factors, for example, demographics (age/experience, sex, occupational group), visual ability (static and dynamic acuity, visual field, field dependence), driving skills (vehicle handing ability, hazard perception, judgement skills), psychological factors (risk tolerance, social/driving deviance, thrill/sensation seeking, sensitivity to external distractions), and temporary states (mood, fatigue, impairment due to drug or drink, illness, stress, speed adoption); (2) delivery task characteristics (length, purpose, shipment type, urgency), vehicle characteristics (performance, comfort, deteriorating status), road settings (road type, speed limit, design speed, maintenance, enforcement levels), environmental factors (time of day, sign/warnings, weather, local knowledge, presence of passengers/pedestrians) (Oppenheim et al , 2016; Santos et al , 2017; Mehdizadeh et al , 2019; Yan et al , 2019; Bowen et al , 2020). Single driving behaviour and road smoothness analytics as mentioned above may not be sufficient; here we are extensively motivated to uncover the significance of external factors that have influences on driving performance gradings.…”
Section: Multiple Factor Analysismentioning
confidence: 99%